2016
DOI: 10.1093/neuonc/now135
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomics to characterize regional genetic heterogeneity in glioblastoma

Abstract: Background. Glioblastoma (GBM) exhibits profound intratumoral genetic heterogeneity. Each tumor comprises multiple genetically distinct clonal populations with different therapeutic sensitivities. This has implications for targeted therapy and genetically informed paradigms. Contrast-enhanced (CE)-MRI and conventional sampling techniques have failed to resolve this heterogeneity, particularly for nonenhancing tumor populations. This study explores the feasibility of using multiparametric MRI and texture analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
178
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(188 citation statements)
references
References 38 publications
5
178
1
1
Order By: Relevance
“…Radiomic studies have used a number of techniques including statistical methods (histogram; gray‐level co‐occurrence matrix [GLCM]; gray‐level difference matrix [GLDM], run length matrix [RLM], gray level size zone matrix [GLSZM], and neighborhood gray tone difference matrix [NGTDM]) with or without Gaussian or Wavelet transformation; and fractal‐based methods across different sequences including T 2 ‐weighted, diffusion‐weighted, and DCE sequences. Initial radiogenomic studies including MRI have been performed in breast cancer renal cell carcinoma and glioma . Variable reproducibility has been shown across different classes of features and further validation work is still required for radiomic biomarkers.…”
Section: Emerging Mri Biomarkersmentioning
confidence: 99%
“…Radiomic studies have used a number of techniques including statistical methods (histogram; gray‐level co‐occurrence matrix [GLCM]; gray‐level difference matrix [GLDM], run length matrix [RLM], gray level size zone matrix [GLSZM], and neighborhood gray tone difference matrix [NGTDM]) with or without Gaussian or Wavelet transformation; and fractal‐based methods across different sequences including T 2 ‐weighted, diffusion‐weighted, and DCE sequences. Initial radiogenomic studies including MRI have been performed in breast cancer renal cell carcinoma and glioma . Variable reproducibility has been shown across different classes of features and further validation work is still required for radiomic biomarkers.…”
Section: Emerging Mri Biomarkersmentioning
confidence: 99%
“…In a study of 48 image‐guided biopsies obtained in 13 tumors, Hu et al demonstrated correlations between conventional, diffusion tensor imaging (DTI), and dynamic susceptibility contrast (DSC) perfusion metrics, and commonly implicated alterations in EGFR, PDGFRA, PTEN, CDKN2A, RB1, and TP53 ( P < 0.03)—with accuracies ranging from 87.5% for RB1 to 37.5% for TP53. A similar study of spatial diversity texture features was able to characterize local EGFR mutation status as well as patient survival in 65 glioblastomas .…”
Section: Brainmentioning
confidence: 99%
“…Multidisciplinary cancer meeting, now enriched by molecular tumor board, constitutes the main pillar for appropriate decision making. In a near future, this multidisciplinary approach will benefit from the ongoing development of new diagnosis strategies such as radiomics, integrating imaging characteristics and genomic data, to refine treatment choice [19]. Addressing patients to clinical trials is critical but major efforts are needed to better select innovating agents at the preclinical level and to carefully design selective clinical trials to evaluate the full potential of targeted-therapies and immune-therapies.…”
Section: Improving Diagnosis and Management Of Primary Brain Tumorsmentioning
confidence: 99%